THE INCREASING OF THE EFFICIENCY OF USING LOW-POTENTIAL HEAT IN ENERGY PRODUCTION - A. A. Solovyev; K. V. Chekarev; D. A. Solovev; L. A. Shilova (Современная наука и инновации, 2022)
The authors consider the options of technical solutions for low-potential heat accumulation systems for water heat carriers of thermal machines. The method of computer modeling of heat-mass transfer and aero-hydrodynamics has been used to calculate the thermal coefficients of cooling the circulating water of power plants in two versions of tower cooling towers with natural draft for longitudinal and counter flow motion of coolants and various arrangements of cooling devices. The primary increase in thermal efficiency in the utilization of low-potential heat in cooling towers with remote heat exchange is established in comparison with traditional cooling towers with internal filling of cooling devices.